Dampak Perilaku Sosial terhadap Pengambilan Keputusan Pembelian Konsumen dalam Industri Telekomunikasi Seluler: Studi Eksperimental di Era Digital dan Pengaruh Media Sosial - Souisa, Novita; Sutomo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Social behavior influences consumer purchase decisions, especially in the mobile telecommunications industry, which is increasingly reliant on social media. Consumers now not only depend on information from companies but also reviews, recommendations, and interactions on digital platforms. This study aims to examine how social behavior, with a focus on the influence of social media, shapes purchase decisions. Using an online survey experimental approach, participants were divided into three groups based on the information received: consumer reviews, expert reviews, and trusted friend recommendations. The results indicate that external information, whether from consumer reviews or experts, promotes faster decision-making, while recommendations from friends have a stronger influence on product choice compared to social media. Although the influence of social media is significant, personal recommendations remain stronger. In the post-purchase phase, external influences no longer alter the decisions already made. These findings provide guidance for telecommunications companies in designing more effective marketing strategies, leveraging social media and personal recommendations to influence purchase decisions.